Analyzing the expected values of neighborhood degree-based topological indices in random cyclooctane chains - Jing, Liang; Yousaf, Shamaila; Farhad, Saira; Tchier, Fairouz; Aslam, Adnan (Frontiers in Chemistry, 2024)
Cyclooctane is classified as a cycloalkane, characterized by the chemical formula C 8 H 16 . It consists of a closed ring structure composed of eight carbon atoms and sixteen hydrogen atoms. A cyclooctane chain typically refers to a series of cyclooctane molecules linked together. Cyclooctane and its derivatives find various applications in chemistry, materials science, and industry. Topological indices are numerical values associated with the molecular graph of a chemical compound, predicting certain physical or chemical properties. In this study, we calculated the expected values of degree-based and neighborhood degree-based topological descriptors for random cyclooctane chains. A comparison of these topological indices' expected values is presented at the end.